Productive efficiency, property rights, and sustainable renewable resource development in the mini-purse seine fishery of the Java Sea - Susilowati, Indah; Bartoo, Norman; Omar, Ishak; Jeon, Yongil; Kuperan, K.; Squires, Dale; Vestergaard, Niels (Cambridge University Press, 2005)
The relationship between productive efficiency and sustainable development of fishing industries in developing countries has received little attention. Ill-structured property rights in common-pool resources lead to a contradiction between private and social technical efficiency, with private and social costs dependent on the level of technical efficiency. Development policies that increase private efficiency can increase the social cost with ill-structured property rights and common-pool resources, and thereby increase social inefficiency. This paper examines this relationship through a case study of the mini purse seine fishery of the Java Sea, and finds that private technical efficiency does not depend on any measurable attributes of human capital, diverges substantially between the peak and off seasons, and differs between vessels more within the off season. © 2005 Cambridge University Press.